Antibacterial Activity of Colloidal Silver against Gram-Negative and Gram-Positive Bacteria - Andrea Vila Domínguez; Rafael Ayerbe Algaba; Andrea Miró Canturri; Ángel Rodríguez Villodres; Younes Smani (MDPI AG, 2020)
Due to the emergence of antimicrobial resistance, new alternative therapies are needed. Silver was used to treat bacterial infections since antiquity due to its known antimicrobial properties. Here, we aimed to evaluate the in vitro activity of colloidal silver (CS) against multidrug-resistant (MDR) Gram-negative and Gram-positive bacteria. A total of 270 strains (Acinetobacter baumannii (n = 45), Pseudomonas aeruginosa (n = 25), Escherichia coli (n = 79), Klebsiella pneumoniae (n = 58)], Staphylococcus aureus (n = 34), Staphylococcus epidermidis (n = 14), and Enterococcus species (n = 15)) were used. The minimal inhibitory concentration (MIC) of CS was determined for all strains by using microdilution assay, and time−kill curve assays of representative reference and MDR strains of these bacteria were performed. Membrane permeation and bacterial reactive oxygen species (ROS) production were determined in presence of CS. CS MIC90 was 4−8 mg/L for all strains. CS was bactericidal, during 24 h, at 1× and 2× MIC against Gram-negative bacteria, and at 2× MIC against Gram-positive bacteria, and it did not affect their membrane permeabilization. Furthermore, we found that CS significantly increased the ROS production in Gram-negative with respect to Gram-positive bacteria at 24 h of incubation. Altogether, these results suggest that CS could be an effective treatment for infections caused by MDR Gram-negative and Gram-positive bacteria.